On time and money donations - Lorenzo Cappellari; Paolo Ghinetti; Gilberto Turati (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper investigates the determinants of time and money gifts. We first develop a behavioural model which accounts for both types of donations, as well as for decisions about domestic and market hours of work. We then investigate the issue empirically, using survey data for Italy. Results suggest that, according to the theoretical predictions, proxies for warm glow, reputational concerns and (impure) altruism are important determinants of giving. Moreover, the unobservable determinants driving money and time donations are positively correlated, suggesting a certain degree of complementarity between the two decisions.
Keywords: J22; D1; 330; volunteering; money donations; household behaviour; Spende; Zeitallokation; Verhalten; Entscheidungstheorie; Schätzung; Italien